Development of a nanoparticle-mediated delivery system to study release of fluorescently-labeled glutamic acid encapsulated in chitosan nanoparticles - Hassan, Ummu Afiqah (2018)
Inefficient cellular delivery and intracellular accumulation are major drawbacks towards achieving favorable therapeutic responses for many therapeutic drugs and biomolecules. To tackle this issue, nanoparticle-mediated delivery vectors have been aptly explored as a promising delivery strategies capable to enhance the bioavailability and cellular localization of biomolecules and therefore, improve their therapeutic efficacies. However, the dynamics of intracellular biomolecule release and accumulation from such nanoparticle systems has remain scarcely studied. Therefore, in this study, chitosan nanoparticle (CNP) was synthesized to serve as the delivery carrier for glutamic acid, a model for encapsulated biomolecules. Various chemical and morphological analyses were conducted to verify the nanoparticle formation and glutamic acid loading. In order to track the glutamic acid release and accumulation, the glutamic acid was then fluorescently-labeled with fluorescein isothiocyanate (FITC) prior encapsulation into CNP. This study therefore describes the encapsulation, release and accumulation of fluorescently labeled-glutamic acid from a robust, non-efficacious chitosan-based nanoparticle delivery system using tripolyphosphate (TPP) as a cross-linker. Light Scattering data concluded the formation of small-sized and monodispersed CNP at a specific volume ratio of chitosan to TPP. Following encapsulation, nanoparticle size increased exponentially to >100 nm to accommodate the glutamic acids within its core. Electron microscopy images revealed a discrete and spherical shape of CNP populations. The particle size increased over 100 nm following glutamic acids loading as reflected by Light Scattering data. Formation of CNP was further reflected by reduction in free amine groups in chitosan, and Fourier Transform Infrared detected peaks of functional groups belonging to both chitosan and TPP. Approximately 60% glutamic acid were efficiently encapsulated into CNP, which further suggested the potential of CNP as a drug delivery vehicle. Cell viability assay demonstrated a low toxicity property of CNP; conferring about 70% cell viability of 786-O cancer cells at the highest concentration used. In vitro tracking of glutamic acids release via fluorescence microscopy revealed a time-dependent release and controlled accumulation of fluorescently modified-glutamic acids from CNP into 786-O cells from 6 hours to 48 hours treatment points. The fluorescently-labeled glutamic acids was found to be release into cells as early as 6 hours post treatment. The fluorescence was gradually increased at 24 hours later and persisted inside the treated cells up to 48 hours. Flow cytometry data demonstrated a gradual increase in intracellular fluorescence signal from 30 minutes to 48 hours post treatment with fluorescently-labeled glutamic acids encapsulated CNP. These results therefore suggested the potential of CNP system towards enhancing the intracellular delivery and release of the encapsulated glutamic acids as well as controlling their accumulation and retention over prolong period of time. This CNP system thus may serves as a potential candidate vector capable to improve the therapeutic efficacy for drugs and biomolecules in medical as well as pharmaceutical applications through the enhanced intracellular release and accumulation of the encapsulated cargo.